2021
DOI: 10.1016/j.xhgg.2021.100042
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropy-guided transcriptome imputation from normal and tumor tissues identifies candidate susceptibility genes for breast and ovarian cancer

Abstract: Summary Familial, sequencing, and genome-wide association studies (GWASs) and genetic correlation analyses have progressively unraveled the shared or pleiotropic germline genetics of breast and ovarian cancer. In this study, we aimed to leverage this shared germline genetics to improve the power of transcriptome-wide association studies (TWASs) to identify candidate breast cancer and ovarian cancer susceptibility genes. We built gene expression prediction models using the PrediXcan method in 681 bre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 57 publications
1
14
0
Order By: Relevance
“…Cis -expression quantitative trait loci (eQTL) and transcriptome-wide association studies (TWASs) leverage associations between risk SNP genotype data and gene expression to identify candidate genes associated with disease risk. To date, 26 candidate genes have been identified as HGSOC candidate risk genes using these methods ( 15 , 37 , 38 ); 16 out of 26 genes (62%) previously identified by HGSOC eQTL or TWAS analyses were also nominated by chromMAGMA ( Fig 2F ). chromMAGMA identified 105 additional genes previously not implicated in HGSOC risk.…”
Section: Resultsmentioning
confidence: 99%
“…Cis -expression quantitative trait loci (eQTL) and transcriptome-wide association studies (TWASs) leverage associations between risk SNP genotype data and gene expression to identify candidate genes associated with disease risk. To date, 26 candidate genes have been identified as HGSOC candidate risk genes using these methods ( 15 , 37 , 38 ); 16 out of 26 genes (62%) previously identified by HGSOC eQTL or TWAS analyses were also nominated by chromMAGMA ( Fig 2F ). chromMAGMA identified 105 additional genes previously not implicated in HGSOC risk.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, the spliceosome-associated factor CTNNBL1, has been related to proliferation and invasion in HGSOC, at least partially through regulation of FOXM1 splicing [ 60 ], Notably, the FOXM1 signaling pathway is activated in 84% high-grade serous ovarian cancer [ 61 ] and linked to platinum resistance [ 62 , 63 ]. Likewise, UQCC1, a protein involved in cytochrome b translation and/or stability, has been recently identified as a candidate ovarian cancer susceptibility gene [ 64 ]. Interestingly, it has been reported that UQCC1 physically interacts with CDR2 [ 65 ], a target antigen of naturally occurring human tumor immunity, widely expressed in the majority of ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…We adjusted raw transcript data for the effects of age, body mass index, top five principal components, and top probabilistic estimation of expression residuals (PEER) factors. In the gene expression data from mammary tissue, we also adjusted for Estrogen Receptor 1 ( ESR1) expression in accordance with previous studies 13,23 . This gene encodes estrogen receptor α, a transcription factor that plays a critical role in regulating gene expression and cell division in mammary glands 33 .…”
Section: Methodsmentioning
confidence: 99%
“…In light of established shared genetic etiology between breast cancer and ovarian cancer 13,[28][29][30][31][32] , here we apply BGW-TWAS to conduct TWAS of each disease (and various subtypes) that consider the regulatory activity of both distal and proximal germline variants for a target gene. We first constructed gene expression imputation models using BGW-TWAS in normal breast and ovarian tissue from the Genotype-Tissue Expression (GTEx) project and subsequently imputed GReX into large-scale GWAS summary data from the Breast Cancer Association Consortium (BCAC) and Ovarian Cancer Association Consortium (OCAC) to identify genes associated with risk of overall breast cancer, five breast cancer subtypes (luminal A-like, luminal B-like, luminal B/HER2-negative-like, HER2-enriched-like, triple-negative), nonmucinous ovarian cancer, and five ovarian cancer subtypes (high grade serous, low grade serous, endometrioid, mucinous, clear cell).…”
Section: Twas Then Tests For Association Between Imputed Gene Express...mentioning
confidence: 99%
See 1 more Smart Citation